Evaluation of The Implementation of The Healthy School Campaign Program at SMP Negeri 191, West Jakarta - Rifa Haya Jaida Yudiana; Mardiana Mardiana (Universitas Negeri Semarang, 2025)
The Ministry of Education and Culture established the Healthy School Campaign to address nutrition and health issues in school children. SMPN 191 is the only junior high school in West Jakarta chosen to run the Healthy School Campaign Program because it uniquely provides educational services. This study aims to evaluate the Healthy School Campaign program at SMPN 191 West Jakarta. This research is descriptive qualitative research using the CIPP evaluation method. Informants were selected through purposive sampling. Data analysis techniques include data reduction, data presentation, and conclusion. The results showed that in the context component, informants already knew the background, objectives, and benefits of implementing Healthy School Campaign Program and were familiar with the Healthy School Campaign Program 2023 guidelines. The input components that are not yet appropriate are funds and available infrastructure. The process component that is not yet appropriate is implementation, because some programs are not routinely implemented and lack supervision. The product component shows that the healthy nutrition program is well implemented, the physical health program is exceptionally well implemented, and healthy immunization is not. The researcher's suggestion for SMPN 191 Jakarta is to run the program regularly and increase program supervision.